Treatment of Distal Fingertip Degloving Injuries Using a Cross-Finger Flap Based on the Dorsal Branch of the Proper Digital Artery at the Middle Phalanx - Feng, Shi-Ming; Gu, Jia-Xiang; Liu, Hong-Jun; Zhang, Nai-Chen; Pan, Jun-Bo; Tian, Heng; Xu, Tao (Journal of Reconstructive Microsurgery, 2013)
This study reports our experience with reconstruction of distal fingertip degloving injuries using a single cross-finger flap based on the dorsal branch of the proper digital artery at the middle phalanx. From January 2009 to October 2011, 18 patients (18 fingers) presented with distal fingertip degloving injuries and were treated with this technique. The mean size of the soft tissue defects was 4.5 cm in length and 2.0 cm in width. The mean size of the cross-finger flaps was 4.7 × 2.1 cm. In the series, all flaps survived completely. No complication was reported, and no further flap debunking procedure was required. At the mean follow-up period of 20.5 months (range, 12–48 mo), the mean static two-point discrimination was 6.3 mm (range, 5–9 mm) of the reconstructed finger pulp. The total range of active motion of the proximal and the distal interphalangeal joints of the donor fingers were 105 and 77.4 degrees, respectively. The cross-finger flap based on the dorsal branch of the proper digital artery at the middle phalanx is a reliable and simple method in reconstruction of distal degloving injuries of the finger.
Keywords: cross-finger flap; dorsal branch of proper digital artery; degloving injury; finger reconstruction